PENGARUH UKURAN PERUSAHAAN, JENIS INDUSTRI, KOMITE AUDIT, DAN UKURAN KAP TERHADAP AUDIT DELAY - Luqman Hakim; Prita Sagiyanti (Universitas Mercu Buana, 2018)
m various parties associated with the company and cause the decline of the company's image in the eyes of investors. This study will test audit delay using firm size factors, industry type, audit committee, and KAP size. This research is a quantitative research with associative causal approach. The population in this research is a company listed on the Indonesia Stock Exchange since 2014-2016. The number of samples in this study as many as 24 companies with 3 times the publication of financial statements (2014-2016) so that obtained samples in this study as 72 corporate data. This researchuses multiple linear regression analysis method with IBM SPSS Version 22 statistical tool. The results of this research show that partially only the type of industry that has a positive and significant impact on audit delay . While firm size variable, audit committee, and KAP size have negative effect not significant to audit delay . Simultaneously firm size, industry type, audit committee, and KAP size have an effect on audit delay.